Androgens increase lws opsin expression and red sensitivity in male three-spined sticklebacks. - Yi Ta Shao; Feng-Yu Wang; Wen-Chun Fu; Hong Young Yan; Kazuhiko Anraku; I-Shiung Chen; Bertil Borg (PLoS ONE)
Optomotor studies have shown that three-spined sticklebacks (Gasterosteus aculeatus) are more sensitive to red during summer than winter, which may be related to the need to detect the red breeding colour of males. This study aimed to determine whether this change of red light sensitivity is specifically related to reproductive physiology. The mRNA levels of opsin genes were examined in the retinae of sexually mature and immature fish, as well as in sham-operated males, castrated control males, or castrated males implanted with androgen 11-ketoandrostenedione (11 KA), maintained under stimulatory (L16:D8) or inhibitory (L8:D16) photoperiods. In both sexes, red-sensitive opsin gene (lws) mRNA levels were higher in sexually mature than in immature fish. Under L16:D8, lws mRNA levels were higher in intact than in castrated males, and were up-regulated by 11 KA treatment in castrated males. Moreover, electroretinogram data confirmed that sexual maturation resulted in higher relative red spectral sensitivity. Mature males under L16:D8 were more sensitive to red light than males under L8:D16. Red light sensitivity under L16:D8 was diminished by castration, but increased by 11 KA treatment. Thus, in sexually mature male sticklebacks, androgen is a key factor in enhancing sensitivity to red light via regulation of opsin gene expression. This is the first study to demonstrate that sex hormones can regulate spectral vision sensitivity.